Five Constituents Contributed to the Psoraleae Fructus-Induced Hepatotoxicity via Mitochondrial Dysfunction and Apoptosis - Guo, Zhaojuan; Li, Pin; Wang, Chunguo; Kang, Qianjun; Tu, Can; Jiang, Bingqian; Zhang, Jingxuan; Wang, Weiling; Wang, Ting (Frontiers in Pharmacology, 2021)
Backgrounds: Psoraleae Fructus (PF)-induced hepatotoxicity has been reported in clinical and animal experiments. However, the hepatotoxic constituents and mechanisms underlying PF-induced toxicity have remained unclear. Therefore, this study explored the potentially toxic PF components and revealed their relative mechanisms. Methods: The hepatotoxicity of PF water (PFW) and ethanol (PFE) extracts was compared using Kunming mice. The different compositions between PFW and PFE, which were considered toxic compositions, were identified using the UHPLC-Q-Exactive MS method. Then, L02 and HepG2 cell lines were used to evaluate the toxicity of these compositions. Cell viability and apoptosis were determined through the Cell Counting Kit-8 (CCK-8) assay and flow cytometry, respectively. An automatic biochemical analyzer detected the aspartate aminotransferase (AST), alanine aminotransferase (ALT), and alkaline phosphatase (ALP). Lastly, we used high-content screening (HCS) to determine the levels of reactive oxygen species (ROS), lipid, and mitochondrial membrane potential (MMP). Results: The ethanol extraction process aggravated the hepatotoxicity of PF, causing more severe injuries. The content of psoralen, isopsoralen, bavachin, psoralidin, bavachinin, neobavaisoflavone, and bakuchiol was higher in the PFE than PFW. Bavachin, psoralidin, bavachinin, neobavaisoflavone, and bakuchiol induced cell apoptosis and the AST, ALT, and ALP leakages. Furthermore, these five constituents increased intracellular lipid accumulation and ROS levels but decreased the MMP level. Conclusion: The ethanol extraction process could induce severe PF hepatotoxicity. Bavachin, psoralidin, bavachinin, neobavaisoflavone, and bakuchiol are the main hepatotoxic ingredients. This mechanism could be associated with oxidative stress and mitochondrial damage-mediated apoptosis. Taken together, this study provides a basis for the clinical application of PF that formulates and improves its herbal standards.